Sekali Duduk Bisa Menulis Huruf Rejang, dengan Teknik Akrostik - Sikulo Sikulo; Dewi Andesti (Universitas Negeri Padang, 2020)
The Rejang letter is often called the KA GA NGA letter, which is the first three letters of the main alphabet. As a letter that should be a matter of pride, of course we must preserve the cultural wealth of our ancestors. This is stated in the 1945 Constitution of the Republic of Indonesia Article 32 paragraph (1) and paragraph (2). Various efforts have been made by the Local Government of Lebong Regency to preserve Rejang Letter, starting from holding seminars by inviting experts and community leaders. Even making Rejang letters a local content in schools, but this has not been able to ground Rejang letters in the Rejang Society, especially reaching millennials as the nation's next generation in Lebong Regency. This is because the right and practical learning techniques have not been found and the reasons why we need to learn the KA GA NGA writing. The study used a qualitative approach with the researcher as a research instrument. The results of this research can be concluded that the acrostic technique allows us to write Rejang letters in the form of sentences quickly.